LOVE LANGUAGE COMMUNICATION IN MAINTAINING RELATIONSHIP HARMONY : STUDY ON MARRIED COUPLES IN KEBUN BUNGA VILLAGE - Khairunisya, Dwi Amanda; Kusnadi, Kusnadi; Fitri, Hartika Utami (Jurnal Konseling Pendidikan Islam, 2025)
The language of love is the right choice for expressing love through communication because with special communication, partners will better understand and understand the intentions of their partner and this can minimize disputes. This research aimed to determine the form of love language communication among husband and wife couples in Kebun Bunga Village and to determine the obstacles that occur between husband and wife in expressing their love language. This research uses qualitative methods and is a type of field research. The results obtained in this research are that husband and wife couples in Kebun Bunga Village have various forms of expression, the dominant love language is quality time. The obstacle faced by married couples in Kebun Bunga Village is the difficulty of expressing love language in the form of words of affirmation, which is caused by psychological factors such as shyness.